Institutional investors, climate disclosure, and carbon emissions - Cohen, Shira; Kadach, Igor; Ormazabal, Gaizka (Journal of Accounting and Economics, 2023)
Exploiting the unique features of the CDP, the world-leading platform of corporate climate risk disclosures, we study the relationship between institutional investors' demand for climate-related information (as reflected in their CDP signatory status), firms' decision to disclose this information, and corporate carbon emissions. We provide systematic international evidence that ownership by CDP signatories is positively associated with the probability of disclosing information to the CDP, and that such disclosure is associated with subsequent lower carbon emissions. We also observe that CDP signatories are more likely to engage with and divest from top emitters disclosing to the CDP. Overall, these results are consistent with the notion that investor demand for climate-related information results in greater corporate disclosure and contributes to firms’ decisions to lower future carbon emissions.